The Implementation of Project Based Learning to Enhance Computational Thinking Ability for Primary School Students - Li Ying; Jiraporn Chano (Journal of Language Learning and Assessment, 2025)
Purpose This study examines the efficacy of Project-Based Learning (PBL) in enhancing Computational Thinking Ability (CTA) among fifth-grade students in Guilin, Guangxi, China, addressing a critical gap in primary education by integrating PBL with computational pedagogy. Grounded in Pappert’s (1980) constructionist theory and Vygotsky’s (1978) sociocultural theory, the research aims to compare CTA development through PBL versus traditional methods, offering insights into innovative teaching strategies aligned with the Curriculum Standards for Information Technology in Compulsory Education (2022) and global digital literacy demands (OECD, 2019). Methodology A quasi-experimental design was employed, involving 60 fifth-grade students from a primary school in Guilin, divided into an experimental group (n=30) using PBL and a control group (n=30) using traditional teaching. The 7-week intervention, conducted from May to July 2025 with 14 class hours, utilized pre- and post-tests, observational checklists, and teacher interviews to assess CTA across decomposition, abstraction, pattern recognition, and algorithmic thinking. Data were analyzed using paired- and independent-samples t-tests. Results/Findings (1) The experimental group’s total CTA mean score increased significantly from 63.43 (SD = 2.81) to 90.74 (SD = 2.43), with effect sizes (Cohen’s d) ranging from 3.36 to 10.32 , indicating substantial within-group improvement; (2) Compared to the control group’s post-test mean of 63.79 (SD = 2.85), the experimental group outperformed with a mean difference of 26.95 (t (58) = 39.45, p < 0.001, d = 10.01) , confirming PBL’s superiority; (3) Among CTA dimensions, pattern recognition showed the largest gain (mean difference = 7.52, d = 8.91), while algorithmic thinking had a smaller effect (d = 2.95), suggesting variability due to limited coding experience. Qualitative feedback supported PBL’s collaborative benefits, though time and resource challenges were noted